Perancangan Design User Interface (UI) untuk Aplikasi Pendeteksi Kebakaran - Renaldi Irwansyah; Ulinnuha Latifa; Yuliarman Saragih (Jurnal Ilmiah Wahana Pendidikan, 2021)
The problem that often occurs so far is the delay in the presence of the fire department at the fire site. This can be caused by three things. First, the officers' lack of preparedness. Second, there was heavy traffic on the road to the scene. Third, the late information received from the home owner. Therefore, a fire extinguishing system must be able to detect signs of fire.The research was conducted to determine the process of sending and receiving data in real time, the delay in sending from the database to the application, and the PEKA design system so that it can be used by the public. The results of the research analysis can be in the form of data received by the database having a delay of about 20 seconds. From the test results, the ESP 8226 WiFi Module can also send data to the database with the help of an internet network hotspot.From the results of this study, it is found that a delay of 20 seconds shows that sending data to and receiving data to the database is very good. The PEKA application design has met specifications, because it has an accuracy value of ≥ 95% and an error of ≤ 5%